Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pariwisata Pada Era Industri 4.0 di Madura - Huzaimah, Nurul; Wildan, Muhammad Alkirom (Jurnal Ilmiah Pariwisata, 2023)
This study aims to determine the effect of work discipline and work environment on employee performance in tourism 4.0 in Madura. This research method uses multiple regression analysis with a quantitative descriptive research type distributing questionnaires to respondents using a Likert scale from 1 to 5. The sample is 96 respondents with accidental sampling. The results of the study show that work discipline and work environment partially have a significant effect on employee performance, because work discipline and work environment are empowered and maintained properly, performance will increase. Conversely, if work discipline and work environment are poor and less attention is paid to it, performance will decrease. For tourism industry leaders in Madura to be more assertive in enforcing rules on employees, the application of a reward and punishment system is expected to be able to create a sense of fear in employees to break the rules as well as be motivated to arrive on time . Keywords : Work Discipline, Work Environment, Employee Performance